2018
DOI: 10.1038/s41598-018-34863-0
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational impacts of bile exposure are mediated by TGR5 signaling pathways

Abstract: Besides their well-known roles in digestion and fat solubilization, bile acids (BAs) have been described as signaling molecules activating the nuclear receptor Farnesoid-X-receptor (FXRα) or the G-protein-coupled bile acid receptor-1 (GPBAR-1 or TGR5). In previous reports, we showed that BAs decrease male fertility due to abnormalities of the germ cell lineage dependent on Tgr5 signaling pathways. In the presentstudy, we tested whether BA exposure could impact germ cell DNA integrity leading to potential impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Moreover, BA-induced down-regulation of adhesion proteins like N-cadherin and connexin 43 (CX43) was shown to alter the BTB, leading to its disruption [ 162 ], making way for more BAs to access the apical compartment and to induce male reproductive dysfunctions by amplifying germ cell degeneration. As observed for male rat fed high-fat diets [ 163 ], it cannot be excluded that BA overload causes persistent alteration in the male germ cell epigenome with an impact on offspring, in accordance with recent studies that have reported generational inheritance of metabolic defects in the offspring of CA-fed fathers [ 164 , 165 ]. Unbiased whole-genome approaches should help to address how BAs code transgenerationally-inherited traits, and complementary studies are still needed to tease out the complex relationship between BAs, their receptors, and male germ cell-derived epigenetic inheritance.…”
Section: Bile Acid/xenobiotic Nuclear Receptors In Testis: Protectsupporting
confidence: 64%
“…Moreover, BA-induced down-regulation of adhesion proteins like N-cadherin and connexin 43 (CX43) was shown to alter the BTB, leading to its disruption [ 162 ], making way for more BAs to access the apical compartment and to induce male reproductive dysfunctions by amplifying germ cell degeneration. As observed for male rat fed high-fat diets [ 163 ], it cannot be excluded that BA overload causes persistent alteration in the male germ cell epigenome with an impact on offspring, in accordance with recent studies that have reported generational inheritance of metabolic defects in the offspring of CA-fed fathers [ 164 , 165 ]. Unbiased whole-genome approaches should help to address how BAs code transgenerationally-inherited traits, and complementary studies are still needed to tease out the complex relationship between BAs, their receptors, and male germ cell-derived epigenetic inheritance.…”
Section: Bile Acid/xenobiotic Nuclear Receptors In Testis: Protectsupporting
confidence: 64%
“…Indeed, prior studies have observed direct effects of bile acids on DNA methylation. 36,37 The composition of specific bile acid species may also contribute to the inflammation-related senescent phenotype. A previous study found that bile acids such as deoxycholic acid contribute to the senescent and inflammatory characteristics of hepatic stellate cells, which combined with high fat feeding leads to fibrosis and hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage has been linked with impairment of cellular capacities and genetic unreliability of ESCs by causing aberrant changes in the stem cell niche . Interestingly, activation of TGR5 by bile acids has a protective effect on germ cell DNA integrity . The protective effects of TGR5 in maintaining the capacities of ESCs implicate that TGR5 is important for protecting the DNA of ESCs against UV‐B‐induced insults.…”
Section: Discussionmentioning
confidence: 99%